A Novel Approach to Primary Cell Culture for Octopus vulgaris Neurons - Maselli, Valeria; Xu, Fenglian; Syed, Naweed I.; Polese, Gianluca; Di Cosmo, Anna (Frontiers in Physiology, 2018)
Octopus vulgaris is a unique model system for studying complex behaviours in animals. It has a large and centralized nervous system made up of lobes that are involved in controlling various sophisticated behaviours. As such, it may be considered as a model organism for untangling the neuronal mechanisms underlying behaviours – including learning and memory. However, despite considerable efforts, Octopus lags behind its other counterparts vis-à-vis its utility in deciphering the cellular, molecular and synaptic mechanisms underlying various behaviours. This study represents a novel approach designed to establish a neuronal cell culture protocol that makes this species amenable to further exploitation as a model system. Here we developed a protocol that enables dissociation of neurons from two specific Octopus’ brain regions, the vertical-superior frontal system and the optic lobes, which are involved in memory, learning, sensory integration and adult neurogenesis. In particular, cells dissociated with enzyme papain and cultured on Poly-D-Lysine-coated dishes with L15-medium and fetal bovine serum yielded high neuronal survival, axon growth, and re-growth after injury. This model was also explored to define optimal culture conditions and to demonstrate the regenerative capabilities of adult Octopus neurons after axotomy. This study thus further underscores the importance of Octopus neurons as a model system for deciphering fundamental molecular and cellular mechanism of complex brain function and underlying behaviours.